Análise de desempenho em um motor flex operando em ciclo Miller a partir da variação da posição angular do comando de válvulas de aspiração e do seu curso de abertura - Igor Cordeiro Trevas (2016)
High price of petroleum-based fuels, in line with increasing pressure from regulatory agencies, creates the need to develop more and more efficient internal combustion engines. For the next few years, taking into account the internal combustion engine, the higher volume of energy efficiency will come from well-known downsizing, which is even more interesting to be combined with the use of biofuels. Another technology to increase the efficiency in internal combustion engines is the possibility of working without the presence of the throttle to control the load, Decreasing pumping losses. This can be done with a fully variable valve timing and stroke where electromechanical devices based on valve camshaft are available and deliver a consumption gain of up to 8%. These devices, if applied to the intake valves allow variation of the closing angle, leading the engine to work according to the theoretical cycles Miller and Otto. Thus, this work aims to study the influence of variation of the intake valve closing angle in the use of Miller (EIVC and LIVC) and Otto cycles. Showing the influence of this variation in fuel conversion efficiency on NOx, CO, CO2 emissions and the main combustion parameters of an internal combustion engine aspirated with theadoption of MultiAir technology applied to intake valves. The study was performed with two different fuels (Gasoline E22 and Ethanol) and under different conditions of rotation and break mean effective pressure, in order to observe how the different work cycles behave with these variations. The study was then carried out with 2000 rpm and 2 bar of break mean effective pressure and engine parameters were compared, then the rotation was maintained at 2000 rpm and the break mean effective pressure was varied at 2, 4 and 6 bar, by the end, the break mean effective pressure was kept at 4 bar and the rotation was varied between 2000, 3000, 4000, 5000 and 6000 rpm. The results obtained when using Miller (EIVC and LIVC) cycle, if compared to the traditional Otto cycle, are advantageous with both fuels tested as well as under all conditions tested, leading to an improvement in fuel conversion efficiency of up to 8% , with reduction in the emission of pollutants and acceptable levels of combustion degradation.